بين هندوتفا واستراتيجيات حكومة ناريندرا مودي- تطهير مسلمي الهند إلى أين؟ - بن عيسى لزهر; دوش الهادي (المجلة الجزائرية للأمن والتنمية Algerian Review of Security and Developement, 2021)
تسعى الورقة البحثية إلى إماطة اللثام عن أهم مظاهر سياسات الإقتلاع والعنف الممارس ضد مسلمي الهند، من خلال إشكالية رئيسية مفادها: ما هي فُرَصُ مسلمي الهند في تطويق أزمة الهجمة الهندوسية الشرسة منذ أواخر العام 2019؟، حيث نفترض أنه: كلما استطاع مسلمي الهند تبني استراتيجية متكاملة، كلما أدّى ذلك إلى تجاوز الهجمة الشرسة لحكومة ناريندرا مودي. حيث اعتمدنا على المنهج الاستقرائي من خلال تتبع الأحداث، وخَلُصنَا إلى أنَّ: التحامل على المسلمين عميق الجذور، و لا مناصة من وحدة الصف لمسلمي الهند وضرورة الاستثمار في الأصوات الداعمة لقضية مسلمي الهند مع( النضال الحقوقي) والتنسيق مع الهيئات الحقوقية الدولية. This paper seeks to expose the most significant manifestations of the eradication policies and violence against Indian’s Muslims by the Narendra Modi government, throw a central question: What are the Indian Muslims’ chances of surrounding the crisis of the fierce Hindu attack since late 2019 ?, we suppose: the more India’s Muslims can adopt an integrated strategy, the more they will go beyond the vicious attack on Narendra Modi’s government. We relied on the induction methods by tracking events, and we concluded that: Prejudice against Muslims is deeply rooted, and must not forgotten by the unity of the Indian ranks Muslims, and the need to invest in the supporting voices of India’s Muslims cause, with (the human rights struggle) and coordination with international human rights bodies.